2018
DOI: 10.1177/0972622518804025
|View full text |Cite
|
Sign up to set email alerts
|

Mediator Analysis of Job Satisfaction: Relationship between Servant Leadership and Employee Engagement

Abstract: Servant leaders attempt altruistically and selflessly to help others before themselves, believe in developing their followers to their greatest potential, and seek to benefit the wider community. The main purpose of the present article is to examine servant leadership as the antecedent to employee engagement, mediated by job satisfaction, in Punjab, using data from 190 employees from different service provider companies (banks, colleges, call centres, insurance companies). Quantitative analysis shows that when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 62 publications
4
24
0
5
Order By: Relevance
“…This finding was comparable to Karatepe and Talebzadeh (2016) who confirmed the essential part of SL in ISSN 2162-3058 2019 improving EE at the same filed in the context of Iran. Furthermore, a significant influence of SL on EE, ES, and ER was found in the present research, similar to the findings of Brohi et al (2018), Kaur (2018), Sepahvand et al (2015), and Hunter et al (2013). The authors reported that SL critically affects EE, ES, and ER.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This finding was comparable to Karatepe and Talebzadeh (2016) who confirmed the essential part of SL in ISSN 2162-3058 2019 improving EE at the same filed in the context of Iran. Furthermore, a significant influence of SL on EE, ES, and ER was found in the present research, similar to the findings of Brohi et al (2018), Kaur (2018), Sepahvand et al (2015), and Hunter et al (2013). The authors reported that SL critically affects EE, ES, and ER.…”
Section: Discussionsupporting
confidence: 91%
“…Some showed that the type of leaderships such as SL could contribute to increasing the opportunity of job engaging at the company (Coetzer et al, 2017). Kaur (2018) confirmed the positive effect of SL on EE. At the same vein, Coetzer et al (2017) approved the considerable link between SL and EE.…”
Section: Servant Leadership and Employee Engagementmentioning
confidence: 84%
See 2 more Smart Citations
“…Hunter et al [38] also provided empirical results for the relationship between servant leadership and employee turnover intentions. Additionally, Wong et al [40] and Kaur [105] showed that servant leadership is positively associated with retention.…”
Section: Employee Engagement As a Mediator Between Servant Leadershipmentioning
confidence: 99%